Postharvest measures during the supply chain to reduce bruises on apples with special reference to India - Golombek, Sabine D; Blanke, Michael M (Journal of Postharvest Technology, 2022)
On-site investigations of postharvest management strategies to reduce bruises in Northern India were carried out in collaboration with the  University of Bonn. India produces more than 2 MT apples (Malus domestica Borkh.) per year and is therefore the fifth-largest apple producer  in the world. Bruises of apples can lead to a substantial wastage and downgrading in fruit quality and are hence a major problem of the apple  industry. The Indian apple industry including the farmers is in a continuous process of reducing losses caused by mechanical damage. Improper  handling from harvest to retail has a high potential to cause bruises. Measures in the supply / value chain to reduce or avoid bruises from harvest  to retail (and improve returns to the stakeholders in the apple industry) are described like precooling, hygiene, chemical treatment, cautious  grading, storage, insulated packing, loading and unloading, careful stacking, transport, resorting, and retail.
Keywords: Apple (Malus domestica Borkh.); bruise; mechanical damage; postharvest management; storage; supply chain; transport